Endothelium and woman: similitude and differences with man - Melgarejo R., Enrique (2014)
There are intra-sexual differences in both endothelial function and dysfunction. Although both sexes share the same hormonal receptors (estrogen and testosterone receptors) these differ in expression. Female estrogen receptors exert vascular protective action through nitric oxide–mediated genomic and non-genomic pathways. Women are ‘protected’ from atherothrombosis until menopause. The abrupt loss of vascular protection leads to a magnification of post-menopausal vascular damage, which is higher when endothelial dysfunction is already present. Women have a less oxidative vascular environment until menopause than men. Women experience more microvascular angina and less myocardial infarction with ST segment elevation, because they display more endothelial dysfunction when risk factors are present. Post-menopausal women develop more prominently systolic hypertension and therefore higher pulse pressure and arterial stiffness, the latter mediated by nitric oxide. Keywords: Endothelium, vascular sex differences, estrogens and